PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN MIE GC JEMBER - Lestari, Dwi Ayu; Mayasari, Fariza Kurnia; Khusniah, Khasin; Safira, Imelda Khairiza; Rumsiyah, Silatur; Qomariah, Nurul (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Mie GC, as one of the popular instant noodle brands in Indonesia, faces the challenge of understanding how these two factors contribute to purchasing decisions and customer satisfaction. One of the main players in this market is Mie GC which has succeeded in attracting consumer interest with various flavor variants and product innovations. Product quality covers various aspects, including taste, texture, packaging, and nutritional value. The aim of this research is to determine the influence of product quality and price variables on consumer satisfaction at "Mie GC" Jember. In this research, we examine the influence of product quality and price on consumer satisfaction with Mie GC using quantitative techniques and survey methods. The population of this research is all buyers who have purchased Mie GC Jember. The sample was determined using the concept of a minimum sample size of nâ‰¥30, so a sample of 35 was determined using the purposive sampling method, namely for buyers who had purchased only once. To find out the respondent's description, descriptive analysis was used. Validity tests and reliability tests are used to test research questionnaires. Multiple linear regression analysis for hypothesis testing. The research results show that product quality influences customer satisfaction at Mie GC Jember. Price also makes a positive contribution to Mie GC Jember customer satisfaction. This research has implications for the concept of customer satisfaction which can increase due to product quality and price.